The Family Life Course and Health: Partnership, Fertility Histories, and Later-Life Physical Health Trajectories in Australia - O'Flaherty, Martin; Turrell, G; Turrell, Gavin; Haynes, Michele; Baxter, Janeen (My University, 2016)
Life course perspectives suggest that later-life health reflects long-term social patterns over an individual's life: in particular, the occurrence and timing of key roles and transitions. Such social patterns have been demonstrated empirically for multiple aspects of fertility and partnership histories, including timing of births and marriage, parity, and the presence and timing of a marital disruption. Most previous studies have, however, addressed particular aspects of fertility or partnership histories singly. We build on this research by examining how a holistic classification of family life course trajectories from ages 18 to 50, incorporating both fertility and partnership histories, is linked to later-life physical health for a sample of Australian residents. Our results indicate that long-term family life course trajectories are strongly linked to later-life health for men but only minimally for women. For men, family trajectories characterized by early family formation, no family formation, an early marital disruption, or high fertility are associated with poorer physical health. Among women, only those who experienced both a disrupted marital history and a high level of fertility were found to be in poorer health.
Keywords: Relationships -- Marriage; Health; Families -- Fertility; Families and relationships; Health and wellbeing; Health; Relationships; Families; Marriage; Fertility; Families and relationships; Health and wellbeing